Narcissism, Life Satisfaction, and Harmony: The Mediating Role of Self-Esteem and Self-Compassion - EKŞİ, HALİL (ANI YAYINCILIK, 2019)
Purpose: The present study aims to investigate the relationships between the two distinct faces of narcissism (admiration and rivalry), the two faces of self-perception (self-esteem and self-compassion) and the two faces of one's evaluation of life ( life satisfaction and harmony in life). Research Methods: The sample of this study consists of university students (N = 381). In this study, Narcissistic Admiration and Rivalry Questionnaire, Self-compassion Scale, Self-esteem Scale, Satisfaction with Life Scale, Life Harmony in Life Scale was employed as data collection tools. The relationship between variables was investigated using Structural Equation Modeling. Results: The structural equation modeling used in this study revealed that self-esteem mediated the relationship between narcissistic admiration, harmony in life, and life satisfaction whereas self-compassion mediated the link between narcissistic rivalry, harmony in life, and life satisfaction. Implications for Research and Practice: Based on the results of this research, it is suggested that additional empirical and longitudinal studies should be conducted. as In this context, individual and group counseling practices aimed at developing self-compassion and self-esteem, increasing life harmony and life satisfaction can be organized. Conclusion: In light of the results obtained in this study, we argue that high levels of narcissistic admiration accompanied by self-esteem may lead to increased harmony in life and life satisfaction. As narcissistic rivalry increases, self-compassion, harmony in life, and life satisfaction decrease. Lower self-compassion may explain the tendency of people higher in narcissistic rivalry to report less harmony in their life and lower life satisfaction. (c) 2019 Ani Publishing Ltd. All rights reserved
Keywords: Narcissistic admiration and rivalry; self-esteem; self-compassion; life satisfaction; harmony in life; positive psychology; ADMIRATION; RIVALRY; SCALE; VALIDATION